Elaboración de néctar de nísperos (Mespillus germanica), con dos tipos de conservantes (benzoato de sodio, sorbato de potasio), y tres endulzantes (panela, miel de abeja, azúcar blanca) en la Universidad Técnica de Cotopaxi 2012-2013 - Socasi Loya, Ana Cristina (2014)
The present research was carried out in the Technical University of Cotopaxi in the Vegetable Raw Material and Industrialization of Fruits Laboratory and Vegetables of the Agroindustrial Engineering Major, it located in Cotopaxi Province, Eloy Alfaro Parish, in the Salache Sector. Where nectar of medlars was elaborated with two additive types (benzoate of sodium, sorbate of potassium) and three edulcorating (panela, honey and white sugar). The research was developed in order to know an innovative product, for the human consumption with good characteristic organoleptic, physical-chemical and microbiology.